Upper airway 3D assessment in CBCT-based orthognathic surgery. (October 2021) - Reis, S.; Chabot, P.; Granucci, M.; Assis, N.; Sales, S.; Campos, F.
Abstract : Objectives: To stratify the maxilla-mandibular movements in the orthognathic surgery treatments of class III patients, assess the volumetric and bidimensional repercussions of these movements in the Upper Airway (UA). Methods: The CBCT data of 44 patients class III, who had undergone orthognathic surgery were collected. After acquisition, the images were recorded and stored in Digital Imaging Communication in Medicine (DICOM) format. Preoperative files (T0) and the 1 to 4 months post-operative files (T1) were obtained. The 3D craniometric evaluation was carried out in the software. In the sinus/airway tool, the total airway pharyngeal nasopharynx, oropharynx, and hypopharynx were delineated, as following the boundaries. In each region, the volume, Minimum Axial Area (MAA) and the area of the respective delineated regions were calculated. The patients were divided into Group I (maxilla 0 to 4.9 mm forward) and Group II (the maxilla 5.0 to 10.0 mm forward). Results: In Group I the correlation between the counterclockwise and the hipopharynx's MAA was moderate (0.439), and for every 1 mm of maxillary advancement obtained a gain of 214.74 mm³ in nasopharynx and 653.90 mm³ in the oropharynx. Conclusion: Maxillary advancement promotes an increase in the upper airway, compensating for a possible constriction that the mandibular setback may promote in the hypopharynx. Small maxillary advancements associated with different mandibular movements promoted greater airway gain.